Meningkatkan Kognitif Mengenal Konsep Bilangan pada Anak Usia Dini melalui Alat Permainan Edukatof (APE) Puzzle di TK Aisyiyah Padang Bintungan, Kecamatan Koto Baru, Kabupaten Dharmasraya - Fadillah, Ayu (Jurnal Sakinah, 2021)
This research is conducted to find out how to improve cognitively recognize the concept of numbers in early childhood through an educative game tool (APE) puzzle at TK Aisyiyah Padang Bintungan. This method in this research is to use descriptive qualitative shortness. Data monthly use observation techniques, interview techniques, and documentation techniques. The analysis uses data triangulation techniques. The results showed that the achievement of development in early childhood is at the stage of developing after teachers carry out cognitive improvement in the concept of numbers in early childhood through the educational game tool (APE) puzzle at Aisyiyah Padang Bintungan Kindergarten.